Real-Time PCR for Measles Virus Detection on Clinical Specimens with Negative IgM Result in Morocco. - Touria Benamar; Latifa Tajounte; Amal Alla; Fatima Khebba; Hinda Ahmed; Mick N Mulders; Abdelkarim Filali-Maltouf; Rajae El Aouad (PLoS ONE)
Since the confirmation of measles cases represents an important indicator regarding the performance of the measles-elimination program, the aim of this study was to evaluate the effectiveness of the routine procedures followed in Morocco for the laboratory confirmation of measles cases. Suspected cases reported between January 2010 and December 2012 were assessed for the timeliness of the sample collection, occurrence of measles clinical symptoms, and the results of the laboratory diagnoses. For 88% of the 2,708 suspected cases, a clinical specimen was collected within 7d of rash onset, of which 50% were IgM-positive and 2.6% were equivocal. The measles symptoms were reported in 91.4% of the cases; the occurrence of symptoms showed a positive association with the serological results (odds ratio [OR] = 2.9883, 95% confidence interval [CI] 2.2238-4.0157). Of the negative samples, 52% (n = 116) tested positive by real-time polymerase chain reaction (PCR). These results are in favor of using molecular detection to complement serological diagnosis in the context of measles surveillance approach in Morocco. In addition, the introduction of additional laboratory methods for differential diagnosis is required for the final classification of suspected cases with maculopapular rash and fever in the context of the measles elimination program.